Influence of the Generator in-Growth Time on the Final Radiochemical Purity and Stability of Tc99m Radiopharmaceuticals. (25th September 2013) - Uccelli, L.; Boschi, A.; Pasquali, M.; Duatti, A.; Di Domenico, G.; Pupillo, G.; Esposito, J.; Giganti, M.; Taibi, A.; Gambaccini, M.
Abstract : At Legnaro laboratories of the Italian National Institute for Nuclear Physics (INFN), a feasibility study has started since 2011 related to accelerated-based direct production of T c 99 m by the 100 Mo(p, 2n)T c 99 m reaction. Both theoretical investigations and some recent preliminary irradiation tests on 100 Mo-enriched samples have pointed out that both the T c 99 g /T c 99 m ratio and the T c 99 m specific activity will be basically different in the final accelerator-produced Tc with respect to generator-produced one, which might affect the radiopharmaceutical procedures. The aim of this work was to evaluate the possible impact of different T c 99 g /T c 99 m isomeric ratios on the preparation of different Tc-labeled pharmaceutical kits. A set of measurements with T c 99 m, eluted from a standard 99 Mo/T c 99 m generator, was performed, and results on both radiochemical purity and stability studies (following the standard quality control procedures) are reported for a set of widely used pharmaceuticals (i.e., T c 99 m -Sestamibi, T c 99 m -ECD, T c 99 m -MAG3, T c 99 m -DTPA, T c 99 m -MDP, T c 99 m -HMDP, T c 99 m -nanocolloids, and T c 99 m -DMSA). These pharmaceuticals have been all reconstituted with either the first [T c 99 m O4 ] − eluate obtained from a 99 Mo/T c 99 m generator (coming from two different companies) or eluates after 24, 36, 48, and 72 hours from last elution. Results show that the radiochemical purity and stability of these radiopharmaceuticals were not affected up to the value of 11.84 for the T c 99 g /T c 99 m ratio.